(untitled) (Journal of Engineering, 2023)
Accurate computation of the roughness coefficient is important in the studies of open channel flow. To measure and identify the hydraulic characteristics of the flow system, the model simulation is necessary to study and get the results of the hydraulic properties to specify Manning coefficient of the Euphrates River. In this study, the reach is extended along the Euphrates River from Haditha Dam to Ramadi Barrage with a distance of 169km. The HEC-RAS model was implemented to simulate the flow within the study reach. The geometry of the river was represented by more than two hundred cross-sections surveyed in 2013 and 2021. The model was calibrated using some observed discharges at the Heet gage station for records of the last five years. The Model was validated using five sets of observed water levels in different cases of manning coefficient in the model. The Root Mean Square Error (RMSE) was used for comparison of the model results. Results of the model showed that the roughness coefficient value for this reach is 0.026 for the river bed and 0.030 for the River bank. These values gave the best coincidence between the simulated and observed values of water levels.